27. OUTCOMES OF ESOPHAGEAL DILATION IN PATIENTS WITH CONGENITAL ESOPHAGEAL ATRESIA AT CHILDREN’S HOSPITAL 2: CASE SERIES (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics and outcomes of esophageal dilation in children with anastomotic strictures following surgery for congenital esophageal atresia at Children’s Hospital 2 from January 2022 to December 2023, with a follow-up period of 6 months.Subjects and methods: A retrospective descriptive case series study. The study subjects were children with esophageal atresia who underwent surgery and were followed up at Children’s Hospital 2, admitted between January 1, 2022, and December 31, 2023.Results: There were 46 patients diagnosed with esophageal atresia, with type C being the most common, accounting for 39 cases (84.8%). Associated congenital anomalies were present in 89% of the patients. Esophageal dilation was performed in 12 (26%) cases due to anastomotic strictures. The median age at the time of dilation was 8 months (1.5–52.5 months). The median number of dilation procedures was 2 (1-3.5), with a minimum of 1 and a maximum of 6 sessions. 7 cases required multiple dilations, with a median interval between dilations of 3.5 months (1–11 months). Dilation methods included Maloney bougies (46.4%), balloon dilation (39.3%), a combination of both methods (25%), and Tucker dilators (8%). The success rate after the first dilation was 42%, after 2–4 sessions was 25%, and after 6 sessions was 8%; 25% of cases were unsuccessful. Other complications included pneumothorax/pleural effusion (39.1%), recurrent pneumonia (19.6%), prolonged wheezing (17.4%), and recurrent tracheoesophageal fistula (6.5%). No fatal complications were reported.Conclusion: Congenital esophageal atresia is often associated with other congenital anomalies. Esophageal dilation using balloons or Maloney bougies are effective and safe methods; however, the rate of restenosis remains high. Attention should be given to managing coexisting conditions and other complications. Additionally, alternative methods, such as esophageal stenting, may be considered.
Keywords: congenital esophageal atresia, anastomotic stricture, esophageal dilation.